The conduction of protons in different stereoisomers of dioxolane-linked gramicidin A channels - Quigley, EP (1999)
Two different stereoisomers of the dioxolane-linked gramicidin A (gA) channels were individually synthesized (the SS and RR dimers;. Science. 244:813-817). The structural differences between these dimers arise from different chiralities within the dioxolane linker. The SS dimer mimics the helicity and the inter- and intramolecular hydrogen bonding of the monomer-monomer association of gA's. In contrast, there is a significant disruption of the helicity and hydrogen bonding pattern of the ion channel in the RR dimer. Single ion channels formed by the SS and RR dimers in planar lipid bilayers have different proton transport properties. The lipid environment in which the different dimers are reconstituted also has significant effects on single-channel proton conductance (g(H)). g(H) in the SS dimer is about 2-4 times as large as in the RR. In phospholipid bilayers with 1 M [H(+)](bulk), the current-voltage (I-V) relationship of the SS dimer is sublinear. Under identical experimental conditions, the I-V plot of the RR dimer is supralinear (S-shaped). In glycerylmonooleate bilayers with 1 M [H(+)](bulk), both the SS and RR dimers have a supralinear I-V plot. Consistent with results previously published (. Biophys. J. 73:2489-2502), the SS dimer is stable in lipid bilayers and has fast closures. In contrast, the open state of the RR channel has closed states that can last a few seconds, and the channel eventually inactivates into a closed state in either phospholipid or glycerylmonooleate bilayers. It is concluded that the water dynamics inside the pore as related to proton wire transfer is significantly different in the RR and SS dimers. Different physical mechanisms that could account for this hypothesis are discussed. The gating of the synthetic gA dimers seems to depend on the conformation of the dioxolane link between gA's. The experimental results provide an important framework for a detailed investigation at the atomic level of proton conduction in different and relatively simple ion channel structures.